Management of Patients Who Make Threats Against Elected Officials: A Case Report - Riess, Paulina; Gonzalez, Luisa; Korenis, Panagiota (Frontiers in Psychiatry, 2018)
Federal law makes it a crime to threaten the President of the United States. The Secret Service conducts thousands of violence risk assessments each year. Literature suggests that 75% of individuals who make threats have been diagnosed with a mental illness (1). Studies show that prominent symptoms in presidential assassins include persecutory and grandiose delusions, hence falling into the category of psychotic disorders. We present a case of a patient diagnosed with Schizoaffective Disorder brought to CPEP (Comprehensive Psychiatric Emergency Program) by the Secret Service for repeatedly dialing 911 and making threats to the President. In the past year the patient had been hospitalized three times for similar behavior. Initial presentation included acute symptoms of psychosis and mania including persecutory delusions, command auditory hallucinations, grandiosity, and thought disorder. Clinicians were faced with unique challenges and consulted the forensic service to navigate the role of the Secret Service and develop a plan to prevent future episodes. The patient was discharged with a court order for treatment, long acting medication, as well as an outpatient appointment. The treatment plan has been effective and the Secret Service has ceased their investigation. We aim to explore issues in patient confidentiality, duty to both report and protect. We will also provide strategies and recommendations for such patients on the inpatient unit.